Roma in tabula - Sophie Madeleine; Jérôme Nicolle (In Situ)
Roma in Tabula is an application which allows everyone to visualize, on mobile devices or computers, part of the research work on the virtual restitution of 4th-century Rome carried out at the University of Caen Normandy. The replica models reflect an as careful and exhaustive as possible analysis of ancient sources (textual, archaeological and iconographical). The choices for replication are explained throughout documentations (primary sources, interpretations, bibliographies…) so that the user can personally evaluate the reliability level of the image. The point is not in any way to impose a historical truth, but rather to offer possible approaches which may be valid at one point in the research process but are still intended to be continually evolving. Virtual reality is an original, funny and instructive way to bring light on traditional academic achievements. In the particular case of the monuments to be found in Rome, the use of augmented reality and of the interactive virtual visit allows a dual approach of the replicated edifices. The augmented reality feature also allows users to see a building rising up in its ancient state (elevations and textures) through the embedded camera. The interactive virtual visit offers a unique immersion experiment on a human scale: light and motion capture systems are used to reproduce the disappeared reality.This paper sets out the scientific framework in which the application has been developed, illustrates the issues of making interactive and documented models available to different communities, and focuses on 3D technologies currently being used.